Inverse Kinematics of a Hyper-Redundant Robotic Manipulator - Ahamad, Syed Masrur; Khan, Md. Raisuddin; Rahman, Md. Mozasser (2008)
Serial robots, Snake or, Worm robots, Tentacle robots or continuum robots are known as hyperredundant robots and possess very large degrees of kinematics redundancy. Inverse kinematics of hyper-redundant robots can have infinite number of solutions, which is a great challenge against position control of such robots. Various techniques have so far been proposed for inverse kinematics of hyper-redundant robots that involve wide range of mathematics, which include nonlinear optimization, Artificial Neural Network, Fuzzy System etc. In this paper a new technique has been proposed that assumes a configuration with a virtual layer, where probable singularities are included. In the successive steps the singularities are removed following some geometric propositions to have the final version of the configuration, which ultimately gives the inverse kinematics of the hyperredundant robot. Mathematics involved in this new technique is the traditional inverse kinematics solution of two link subrobots, which are selected to satisfy the geometric propositions. The proposed technique has been tested on four link and six link robots and some comparison are made with one of the recent techniques known as ANFIS.